Patterns of wonder : inviting emergent writers to play with the conventions of language - La Rocca, Whitney; Anderson, Jeff, 1966- (Stenhouse Publishers, 2021)
"Patterns of Wonder continues the conversations based in Jeff Anderson's invitational process for teaching grammar that began with Everyday Editing and was made applicable through our widely successful Patterns of Power family of books (POP, ePOP, POP+, and mPOP). In this book, Whitney and Jeff apply the series' basic principles of noticing, conversation, and application around the moves professional authors make to engage the playful wonderings of our youngest (emergent) writers"-- Provided by publisher.
Keywords: English language -- Grammar -- Study and teaching (Primary); English language -- Grammar -- Study and teaching (Kindergarten); English language -- Composition and exercises -- Study and teaching (Primary); English language -- Composition and exercises -- Study and teaching (Kindergarten); Anglais (Langue) -- Composition et exercices -- Étude et enseignement (Primaire)